Walking on the gender tightrope: Unlocking ESG potential through CEOs' dynamic capabilities and strategic board composition - Tim Heubeck (Business Strategy and the Environment, 2023)
This study explores the relationship between chief executive officers (CEOs) and the board of directors in the context of environmental, social, and governance (ESG) performance. Based on a multi-theoretical approach, it examines whether dynamic CEO capabilities (DCCs) facilitate ESG performance by enabling capable CEOs to navigate complex stakeholder expectations effectively. Additionally, the impact of board gender diversity (BGD) on this relationship is tested, given its significance for ESG-related decision-making. Longitudinal analysis of S&P 900 manufacturing firms demonstrates that strong DCCs positively influence ESG performance, supporting dynamic managerial capabilities and upper echelons theories within the institutional and shareholder theory frameworks. The findings also corroborate that BGD has a moderating effect, initially strengthening the DCC–ESG relationship, in line with gender socialization and diversity theories. However, the study reveals a threshold effect, where ESG benefits from DCCs diminish once BGD reaches approximately 35%, providing a new perspective on critical mass theory.
Keywords: 330; board of directors; chief executive officer; corporate sustainability; dynamic managerial capabilities; ESG; upper echelons theory